Olympic medals as fruits of comparison?: Assimilation and contrast in sequential performance judgments - Damisch, Lysann; Mußweiler, Thomas; Plessner, Henning (Journal of experimental psychology, 2006)
The authors investigated the evaluative consequences of sequential performance judgments. Recent social comparison research has suggested that performance judgments may be influenced by judgments about a preceding performance. Specifically, performance judgments may be assimilated to judgments of the preceding performance if judges focus on similarities between the two. If judges focus on differences, however, contrast may ensue. The authors examined sequential performance judgments, using data gathered from the 2004 Olympic Games as well as data gathered in the laboratory with students or experienced gymnastics judges as participants. Sequential performance judgments were influenced by previously judged performances, and the direction of this influence depended on the degree of perceived similarity between the successive performances.
Gesehen am 22.07.2022